ALTERATION IN THE ACTIVITIES OF A FEW ENZYMES IN THE LIVER OF HOUSE SPARROW, PASSER DOMESTICUS (LINNAEUS) EXPOSED TO MERCURIC CHLORIDE - MAGON, VIJAY K.; GARG, S. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
The effect of mercuric chloride (5.0 uglone bird, weighing 19.95 - 0.51 gm) on the enzymes in liver of house sparrow, P. domesticus was observed at 5, 10 and 20 days. The activity of alkaline phosphatase enzyme decreased after the treatment period in comparison to control. Acid phosphatase and glucose-6-phosphatase activity increased significantly (P<0.05) at the 5 days stage, however, after the 10 and 20 days stages it was decreased (P - 0.001). The activity of succinic, lactic and pyruvic dehydrogenases decreased (P - 0.01) in all the stages in comparison to control one.